INOVASI USAHATANI TEMBAKAU DI KECAMATAN KLEDUNG, KABUPATEN TEMANGGUNG - Arif Sofianto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
Tobacco farmers face many obstacles that complicate their farming. There are at least two important situations that occur at this time, the firstly problem of limited resources, namely land tenure which is relatively narrow, and both farm management issues, related to capital, and institutional markets. The purpose of this study are: 1). Identifying the necessary social innovation strategy for tobacco farmers independence and prerequisites to do so, 2). Identify the necessary technological innovation strategies for tobacco farmers independence and and prerequisites to do so. The research is analytical descriptive research with a qualitative approach. Research conducted in the District of Kledung, Temanggung Regency, data sources or informants are tobacco farmers, extension workers and local government officials concerned. Analysis technique used is the analysis modep Spradley. The conclusion of this study are: 1). Social innovation strategy as the solution of problems faced by farmers consist of organizing, strengthening the bargaining position, and the strengthening of capital, and prerequisite for realizing social innovation in the tobacco farmers is the development of knowledge, awareness, social life, social networking, leadership and social control, 2). Technological innovations for independence tobacco farmers is the optimization of resources, diversification and efficiency of agriculture, and prerequisites for technology innovations include the provision of information, education or development and implementation of technological provision of resources.